Tree holes as larval habitats for Aedes aegypti in public areas in Aguaray, Salta province, Argentina - Mangudo, Carolina (2011)
Natural water holding cavities such as tree holes where Aedes aegypti larvae may develop have been mostly overlooked in South America, in spite of dengue occurrence. The objective of this study was to determine if mosquitoes use water filled tree holes in Aguaray, Salta province. This locality of northwest Argentina is located on a principal terrestrial transport and commercial route connecting northwest Argentina with Bolivia, the main route of introduction of dengue to northwest Argentina, and where large dengue outbreaks have been recently recorded. 186 trees were examined of which 11 of had holes that held water. Thirty larvae were found in 5 of 12 water holding holes, 4 pupae were collected from 3 holes, and all of them were Ae. aegypti. Even though productivity of tree holes may be low, nevertheless they may contribute to maintenance of populations of Ae. aegypti and become relevant as reinfestation sources if monitoring and vector control are not sustained.